Penyuluhan Pencegahan Stunting pada Anak Balita di Kelurahan 16 Ulu Tahun 2024 - Santi Rosalina; Heriziana Heriziana (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting is a major threat to the quality of Indonesian people, as well as a threat to the nation's competitiveness. This is because Stunted children not only have their physical growth disrupted (short stature/stunt), but also their brain development is disrupted, which of course will greatly affect their abilities and achievements at school, productivity and creativity at productive ages.